Opportunities and challenges for mangrove restoration in the Mekong Delta: Status, policies and stakeholder outlook - Pham Thu Thuy; Vien, N.N.; Vo, Q.T.; Tang, T.K.H.; Nguyen, T.L.; Tran, N.M.H.; Nguyen, T.T.A.; Nguyen, T.V.A.; Nguyen, N.Q. (Center for International Forestry Research, 2022)
Based on a literature and policy review, spatial analysis, participatory mapping and stakeholder consultations, this paper identifies potential sites for mangrove restoration; looks at policy planning, possibilities for natural regeneration, and stakeholder perceptions; and discusses opportunities and challenges for mangrove restoration in the Mekong Delta, Vietnam.